PEMBERIAN EDUKASI KEPADA ORANG TUA DAN KADER DALAM PEMBERIAN VARIAN MENU MAKAN PADA BALITA UNTUK MENURUNKAN STUNTING DI PUSKESMAS ALUH-ALUH BESAR - Deananda; Utami, Syahrida Wahyu; Lestari, Nur Cahyani Ari (LPPM Universitas Ibnu Sina, 2026)
Stunting is a serious public health problem in Indonesia, with prevalence reaching 21.5% in 2023. Banjar District, South Kalimantan, recorded a stunting prevalence of 30.1%, well above the national target of 14% in 2024. This condition is caused by various factors, including inadequate parenting patterns, insufficient nutritional intake, and limited parental knowledge about providing varied food for children. This community service activity aims to provide education to parents and cadres about providing varied menu options for toddlers to reduce stunting in the working area of Aluh-Aluh Besar Health Center, Banjar District. The method used is educational outreach with leaflets and flip charts, accompanied by interactive discussions with participants. The activity involved 41 participants, consisting of parents and posyandu cadres. The results of the activity showed an increase in participants' understanding of the importance of providing varied food containing balanced nutrition, the role of parenting in stunting prevention, and exclusive breastfeeding practices. Activity outputs include seminar results and journal publications in accredited national journals. In conclusion, educating parents and cadres is an important intervention in efforts to prevent and reduce stunting in the community.